Simplifying
6a + -8 = 4a + 6
Reorder the terms:
-8 + 6a = 4a + 6
Reorder the terms:
-8 + 6a = 6 + 4a
Solving
-8 + 6a = 6 + 4a
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-4a' to each side of the equation.
-8 + 6a + -4a = 6 + 4a + -4a
Combine like terms: 6a + -4a = 2a
-8 + 2a = 6 + 4a + -4a
Combine like terms: 4a + -4a = 0
-8 + 2a = 6 + 0
-8 + 2a = 6
Add '8' to each side of the equation.
-8 + 8 + 2a = 6 + 8
Combine like terms: -8 + 8 = 0
0 + 2a = 6 + 8
2a = 6 + 8
Combine like terms: 6 + 8 = 14
2a = 14
Divide each side by '2'.
a = 7
Simplifying
a = 7